Correction of the Allan-Herndon-Dudley syndrome-causing SLC16A2 mutation G401R in a patient derived hiPSC line - Katarzyna A. Ludwik; Robert Opitz; Sabine Jyrch; Matthias Megges; Peter Kühnen; Harald Stachelscheid (Stem Cell Research)
The X-linked Allan-Herndon-Dudley syndrome (AHDS) is a genetic disorder characterized by severe psychomotor impairment, resulting from mutations in the SLC16A2 gene, which encodes the thyroid hormone transporter MCT8 (monocarboxylate transporter 8). Previously, we established a hiPSC line from a patient carrying the SLC16A2:R401G mutation (BIHi045-A). Using CRISPR/Cas9-mediated gene editing, we targeted exon 3 of SLC16A2 and used single-stranded oligodeoxynucleotides as homology-directed repair templates to correct the R401G missense mutation, generating an isogenic control cell line.